Differences in the global exposure, mortality and disability of low bone mineral density between men and women: the underestimated burden in men - Binxiang Zhu; Shian Hu; Jianfeng Guo; Zijian Dong; Yimin Dong; Feng Li (BMC Public Health, 2023)
Abstract Talking about osteoporosis, we tend to focus on post-menopause women who are at increased risk due to estrogen depletion, while less attention has been paid to the disease in men. Currently, there is a lack of understanding about the difference of osteoporosis incidence and burden by sex. In this study, we used data from the Global Burden of Disease Study 2019 (GBD 2019) to compare the difference in the prevalence and burden of low bone mineral density (LBMD) between men and women, by location, year, age and socio-demographic index. We found the prevalence of LBMD was higher in women than in men. However, the age standardized mortality rate was greatly higher in men than in women. Using disability-adjusted life year (DALY) to measure the burden, we also observed higher age standardized DALY rate in men. Using sociodemographic index (SDI) as the measure of social development level, we found that higher mortality and DALY rates were mainly seen in middle and high SDI countries. Falls were the leading cause for of deaths and disabilities in both men and women with LBMD, followed by transport injuries. Fall-related mortality was higher in women, while transport injuries caused more deaths and disabilities in men. Conclusively, more attention should be paid to osteoporosis in men, and related policies, clinical practices, and guidelines are in need to reduce the burden of LBMD and osteoporosis in men.